UPAYA MELESTARIKAN BUDAYA RELIGIUS MELALUI PEMBIASAAN BERDOA DAN MEMBACA ASMAUL-HUSNA BERSAMA SEBELUM PEMBELAJARAN DI MTS MATSARATUL HUDA PANEMPAN PAMEKASAN - Errohmah , Fina Witrin; Wahyudi, Kacung (re-JIEM (Research Journal of Islamic Education Management), 2021)
1) efforts to preserve religious culture troughth the management of the habit of praying and reading asmaul husna togerther before learning at MTs Matsaratul Hudan Panempan Pamekasan, 2) impact efforts to preserve religious culture troughth the management of the habit of praying and reading asmaul husna togerther before learning